The Influence of Qira'at Variants in Interpretation Ayat-Ayat Al-Qur’an - Ghozi Febra; Admizal, Iril; Suriyadi (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study examines the influence of Qira'at variations on the interpretation of Quranic verses, focusing on the potential implications for understanding and applying Islamic teachings. Qira'at refers to the various ways in which the Quran is recited, with different schools of thought and traditions offering distinct readings of the sacred text. The research aims to investigate how these variations affect the interpretation of specific Quranic verses, exploring the potential consequences for Islamic thought and practice. Through a comprehensive analysis of existing literature and primary sources, this study identifies key differences in Qira'at readings and their corresponding impacts on the interpretation of Quranic verses. The findings highlight the significance of considering Qira'at variations in the context of Islamic scholarship and the potential for these differences to shape the understanding and application of Islamic teachings. The study contributes to the ongoing discussion on the role of Qira'at in Islamic studies, emphasizing the importance of acknowledging and addressing the implications of these variations on the interpretation of Quranic verses. The research also provides a framework for further exploration of the relationship between Qira'at and Islamic thought, with potential applications in fields such as Islamic studies, theology, and interfaith dialogue.